2009
DOI: 10.1159/000248762
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tonapofylline (BG9928), an Adenosine A<sub>1</sub> Receptor Antagonist, against Cisplatin-Induced Acute Kidney Injury in Rats

Abstract: Background/Aims: Cisplatin (CIS) induces nephrotoxicity partly through renal vasoconstriction and decreased glomerular filtration effects thought to involve adenosine acting on adenosine A1 receptors (A1Rs). We studied the effect of the orally active, A1R antagonist tonapofylline (BG9928) on biochemical measures of renal function in CIS-induced acute kidney injury (AKI) in rats. Methods: Tonapofylline, 1 mg/kg b.i.d., p.o., was administered on days 0–1 or 0–6 to rats treated with CIS 5.5 mg/kg i.v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Also, tubules with regenerative changes were observed. These changes run parallel with the findings documented by previous researchers [24,26,27] who stated morphological changes consistent with acute nephrosis within the cortex.…”
Section: Discussionsupporting
confidence: 90%
“…Also, tubules with regenerative changes were observed. These changes run parallel with the findings documented by previous researchers [24,26,27] who stated morphological changes consistent with acute nephrosis within the cortex.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that adenosine may be involved in the haemodynamic changes in the kidney induced by cisplatin [128]. Cisplatin upregulates A 1 receptors in rat kidney [25] and A 1 receptor antagonists have a protective effect against cisplatininduced acute kidney injury in rats [107]. Adenosine antagonists have protective effects against acute renal failure [156, 253,358].…”
Section: Nephrotoxicant Injurymentioning
confidence: 99%
“…These results of these studies suggest that L-97-1 may provide protection to the kidney by increasing renal blood flow. Furthermore, adenosine A 1 receptor antagonists block cisplatin induce nephrotoxicity (Gill et al, 2009; Knight et al, 1991; Nagashima et al., 1995). In one study, the adenosine A 1 receptor antagonist, tonapofylline (BG 9928), significantly reduced elevated levels of serum BUN and creatinine and improved renal pathology scores, including reducing interstitial inflammation (Gill et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adenosine A 1 receptor antagonists block cisplatin induce nephrotoxicity (Gill et al, 2009; Knight et al, 1991; Nagashima et al., 1995). In one study, the adenosine A 1 receptor antagonist, tonapofylline (BG 9928), significantly reduced elevated levels of serum BUN and creatinine and improved renal pathology scores, including reducing interstitial inflammation (Gill et al, 2009). Thus in sepsis, by blocking activation of adenosine A 1 receptors in the lung and the kidney, an adenosine A 1 receptor antagonist may improve outcome by attenuating acute lung injury and maintaining renal blood flow and function.…”
Section: Discussionmentioning
confidence: 99%